Factors associated with cyber-victimization among immigrants and non-immigrants in Canada: a cross-sectional nationally-representative study - Kathleen S. Kenny; Lisa Merry; Douglas A. Brownbridge; Marcelo L. Urquia (BMC, 2020)
Abstract Objectives There is a paucity of research on patterns of cyber-victimization in minority groups, including immigrants. This study aimed to identify individual, interpersonal and contextual characteristics associated with cyber-victimization among immigrants and non-immigrants. Methods We drew on nationally representative data from adolescents and adults in the Canadian General Social Survey on victimization (2014). We used multivariable logistic regression to identify potential factors associated with cyber-victimization in the last 12 months, stratified by immigrant status and sex. Results Among 27,425 survey respondents, the weighted prevalence of cyber-victimization in the last 12 months was 2.1% among immigrants and 2.3% among non-immigrants. Cyber-victimization rates differed significantly by sex among immigrants (2.8% for males vs. 1.4% for females), but not among non-immigrants (2.1% for males vs. 2.4% for females). While most other factors associated with cyber-victimization were similar for immigrants and non-immigrants, there were pronounced associations of past child maltreatment (adjusted prevalence odds ratio [aPOR] 4.85, 95% confidence interval [CI] 2.76, 8.52) and residence in an unwelcoming neighbourhood (aPOR 5.08, 95% CI 2.44, 10.55) with cyber-victimization among immigrants that were diminished or absent among non-immigrants. Additionally, sex-stratified analyses among immigrants showed cyber-victimization to be strongly associated with having a mental health condition (aPOR 3.50, 95% CI 1.36, 8.97) among immigrant males only, and with perceived discrimination (aPOR 4.08, 95% CI 1.65, 10.08), as well as being under 24 years old (aPOR 3.24, 95% CI 1.09, 9.60) among immigrant females. Conclusions Immigration status and sex were differentially associated with cyber-victimization. Findings support the salience of a social-ecological perspective and gender-stratified analyses to better elucidate complex pathways linking cyber-victimization to potential gender-based health inequities among immigrants.